Предотвращение пожароопасного действия электрического тока в электропроводках напряжением 220 В - Aushev, Игорь (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The dependence of the heating time of insulation for stranded conductor up to the maximum allowable temperature by electrical current has been determined. A method for selecting protection of the electric wiring devices, which is based on a comparison of time-current characteristics of protective devices and cable products and use the resulting dependence for the heating cable products on the flowing current, has been developed.